Mutation in the 26S proteasome regulatory subunit rpn2 gene in Plasmodium falciparum confers resistance to artemisinin - Gonçalves, Adriana F.; Lima-Pinheiro, Ana; Teixeira, Miguel; Cassiano, Gustavo Capatti; Cravo, Pedro; Ferreira, Pedro E. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Malaria parasites increasingly develop resistance to all drugs available in the market, hampering the goal of reducing malaria burden. Methods Herein, we evaluated the impact of a single-nucleotide variant, E738K, present in the 26S proteasome regulatory subunit rpn2 gene, identified in Plasmodium chabaudi resistant parasites. Plasmids carrying a functional rpn2 interspecies chimeric gene with 5’ recombination region from P. falciparum and 3’ from P. chabaudi were constructed and transfected into Dd2 P. falciparum parasites. Results and discussion The 738K variant parasite line presented increased parasite survival when subjected to dihydroartemisinin (DHA), as well as increased chymotrypsin-like activity and decreased accumulation of polyubiquitinated proteins. We thus conclude that the ubiquitin-proteasome pathway, including the 738K variant, play an important role in parasite response to DHA, being the first report of a mutation in a potential DHA drug target enhancing parasite survival and contributing to a significant advance in the understanding the biology of artemisinin resistance.